(untitled) (Fiep Bulletin - online, 2015)
The purpose of this study was to evaluate the fine motor skill (FMS) and gross motor skill (GMS) in children and to identify the relation between Motor Age (MA) from FMS and GMS and Chronological Age (CA). Participated of this study 26 children from 2 through 6 years old, boys and girls, students from Centro de Educação Infantil Pequeno Iapar, located at Londrina-Pr. The Motor Evaluation Manual (ROSA NETO, 2002) was used as the instrument to collect the data. The task was presented to the children in base of their chronological age, going forward or backward if they were successful or not. The Spearman’s coefficient identified a significant correlation (rho=0,856; p=0,000) between CA and FMS and (rho=0,857; p=0,000) between FMS and GMS between CA and GMS and (rho=0,796; p=0,000) between FMS and GMS. Wilcoxon’s test found significant difference between FMS (Z=2,501; p=0,012 and GMS (Z=3,923; p=0,000). The GMS and FMS development was linearly related to CA, which can indicate that children would be predisposed to develop in direction to skilled movements. We suggest the realization of new studies that should investigate the influence of environment, materials and Physical Education classes on FMS and GMS